2015
DOI: 10.1113/jp270307
|View full text |Cite
|
Sign up to set email alerts
|

Motor units in the human medial gastrocnemius muscle are not spatially localized or functionally grouped

Abstract: Key pointsr Human medial gastrocnemius (MG) motor units (MUs) are thought to occupy small muscle territories or regions, with low-threshold units preferentially located distally.r We used intramuscular recordings to measure the territory of muscle fibres from MG MUs and determine whether these MUs are grouped by recruitment threshold or joint action (ankle plantar flexion and knee flexion).r The territory of MUs from the MG muscle varied from somewhat localized to highly distributed, with approximately half th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
2
29
1
Order By: Relevance
“…Even though the results presented by Héroux et al . () suggest the territory of single motor units may span proximo‐distal regions as large as the gastrocnemius length, they did not access the distribution of fibres within the territory. Interestingly, in relation to the noise level, the amplitude of action potentials of individual motor units was different across detection sites; potentials with greater amplitude seem to have been detected locally, i.e.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Even though the results presented by Héroux et al . () suggest the territory of single motor units may span proximo‐distal regions as large as the gastrocnemius length, they did not access the distribution of fibres within the territory. Interestingly, in relation to the noise level, the amplitude of action potentials of individual motor units was different across detection sites; potentials with greater amplitude seem to have been detected locally, i.e.…”
mentioning
confidence: 95%
“…The detailed work presented by Héroux et al . () clearly provides good insight into the behaviour of small populations of motor units along medial gastrocnemius during relatively low level isometric contractions. Employing intramuscular EMG to study individual motor units does not, however, enable the study of a spectrum of functionally significant, mechanically demanding tasks, nor does it allow the full spectrum of motor units to be included in the evaluation (i.e.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…We recently showed that low to medium threshold motor units in the human medial gastrocnemius muscle have territories that vary widely in size, from a few centimetres to the full length or width of the muscle (Héroux et al . ). In their Letter, Vieira et al .…”
mentioning
confidence: 97%